Analisis Fitur Pengguna Shopee Paylater Terhadap Kepuasan Pelanggan (Studi Kasus : Mahasiswa Manajemen Kelas VllC, Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara Medan) - Budi Dharma; Mira Nur Aisah; Mentari Kinanti Surya Sirait (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
: Shopee PayLater is a feature in the SHOPEE application which has a method with a "buy pay later" system. This method is provided by Shopee with OJK supervision. Which is of course safe for users, data that has security when all conditions are met. This research aims to find out and analyze the Shopee PayLater feature, both from its advantages and disadvantages and to find out user feedback on the Shopee PayLater feature on (Case study on Class Vll C Management Students at UINSU). This research was conducted through a qualitative method, namely the case study approach. Data collection techniques used were observation and interviews. The data analysis technique used is data information, data presentation, conclusion/verification. The research results provide evidence that: (1) The Shopee PayLater feature is a loan in the form of a limit, which has a character almost like a virtual credit card. (2) Disbursement of the credit limit on Shopee PayLater is disbursing the existing limit amount on Shopee PayLater into nominal money and not goods. Which is adjusted to what items you want to check out and pay using PayLater, immediately deducted according to the nominal ordered. (3) The advantages and disadvantages of the Shopee Paylater feature, the advantages include: Of course, it's easy to apply, you can shop now but pay later, the limit can continue to increase if the user is always active shopping, Shopee Paylater users can often get free shipping promos, as well as features Shopee Paylater is supervised by the OJK, customer security is also guaranteed, while the drawbacks of Shopee Paylater include using an interest system and handling fees, there is no tolerance for delays in payments and paylater can cause users to become consumptive. (4) User feedback on the use of the Shopee Paylater feature, including loyal users to Shopee Paylater, users giving positive recommendations to people around them and the company (Shopee) are also the main considerations for users when they want to use paylater. The conclusion of this study is that Shopee Paylater as a loan feature in the form of providing a credit limit is able to provide many benefits for its users, so that users feel satisfied when using Shopee Paylater.